1999
DOI: 10.1086/501661
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prevention by High-Efficiency Particulate Air Filtration or Laminar Airflow Against Aspergillus Airborne Contamination During Hospital Renovation

Abstract: This study showed a strong association between building renovation and an increase in environmental Aspergillus contamination. Results confirmed the high efficacy of laminar airflow plus HEPA filtration and a high air-change rate. Although filtration with HEPA was effective during normal conditions, it alone was unable to prevent the rise of Aspergillus contamination related to building renovation. This study emphasized the necessity of an environmental survey of airborne contamination related to construction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…This theme included four studies [20][21][22][23] that evaluated the effi cacy of HEPA fi lters in reducing the fungal concentration in the air in hemato-oncology units but did not address patient outcomes. Two of the studies found that HEPA fi lter performance was no better than regular air fi ltration 20,21 .…”
Section: Effi Cacy Of Hepa Fi Lters In Reducing the Fungal Concentratmentioning
confidence: 99%
“…This theme included four studies [20][21][22][23] that evaluated the effi cacy of HEPA fi lters in reducing the fungal concentration in the air in hemato-oncology units but did not address patient outcomes. Two of the studies found that HEPA fi lter performance was no better than regular air fi ltration 20,21 .…”
Section: Effi Cacy Of Hepa Fi Lters In Reducing the Fungal Concentratmentioning
confidence: 99%
“…[10][11][12][13] However, the benefits conferred by HEPA filtration require appropriate maintenance, monitoring of positive pressure and education of staff and patients. [14][15][16] Previous colonisation or invasive fungal infection during periods of chemotherapy-induced neutropenia increase the risk of re-emergence of infection in the post transplant period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Cornet et al, 15 the spore counts increased sixfold in haematological patient rooms with HEPA filtration alone, but remained stable in the HEPA-LAF ventilated patient rooms. A correlation has been seen between fungal spore counts and the incidence of IA.…”
Section: Construction and Aspergillosis In A Bmt Unitmentioning
confidence: 91%